Three days in june ebook A novel. - Tyler, Anne (2025)
“What a treat.” — Washington Post “Simply exquisite.” —Liane Moriarty “Nobody understands human nature better than Tyler. And nobody understands the complexities of love the way she does.” — Boston Globe “ Three Days in June is like reading a hug.” — Minneapolis Star Tribune NEW YORK TIMES BESTSELLER • A new Anne Tyler novel destined to be an instant classic: a socially awkward mother of the bride navigates the days before and after her daughter's wedding. Gail Baines is having a bad day. To start, she loses her job—or quits, depending on whom you ask. Tomorrow her daughter, Debbie, is getting married, and she hasn’t even been invited to the spa day organized by the mother of the groom. Then, Gail’s ex-husband, Max, arrives unannounced on her doorstep, carrying a cat, without a place to stay, and without even a suit. But the true crisis lands when Debbie shares with her parents a secret she has just learned about her husband to be. It will not only throw the wedding into question but also stir up Gail and Max’s past. Told with deep sensitivity and a tart sense of humor, full of the joys and heartbreaks of love and marriage and family life, Three Days in June is a triumph, and gives us the perennially bestselling, Pulitzer Prize–winning writer at the height of her powers.